2014
DOI: 10.1007/s12288-014-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Zidovudine Induced Anaemia in HIV Infected Patients in Southern Odisha

Abstract: Zidovudine (AZT), a nucleoside reverse transcriptase inhibitor was the first breakthrough in AIDS therapy in 1990.This study was conducted with an aim to determine prevalence of AZT induced anaemia in HIV infected patients initiated on AZT containing anti retroviral therapy(ART) regimen and also to find out any risk factor for causing AZT induced anaemia. Study was carried out in ART centre, M.K.C.G, MCH, Berhampur between Jan 2009 and Dec 2011. HIV infected patients registered at ART centre were treated accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
3
5
1
1
Order By: Relevance
“…In patients taking ZDV containing regimen anemia was independently predicted by the; advanced AIDS stage at baseline, advanced baseline immune suppression, cotrimoxazole prophylaxis (CPT) intake, poor adherence status, and undernutrition at baseline. This finding is in agreement with the study conducted in Thailand, 27 which reported, anemia was independently predicted by low baseline CD4 count, low BMI, and advanced AIDS stage at enrolment. The possible explanation for this association may be that HIV patients with low CD4 count are known to be at risk of multiple opportunistic infections, which are known to cause anemia.…”
Section: Discussionsupporting
confidence: 93%
“…In patients taking ZDV containing regimen anemia was independently predicted by the; advanced AIDS stage at baseline, advanced baseline immune suppression, cotrimoxazole prophylaxis (CPT) intake, poor adherence status, and undernutrition at baseline. This finding is in agreement with the study conducted in Thailand, 27 which reported, anemia was independently predicted by low baseline CD4 count, low BMI, and advanced AIDS stage at enrolment. The possible explanation for this association may be that HIV patients with low CD4 count are known to be at risk of multiple opportunistic infections, which are known to cause anemia.…”
Section: Discussionsupporting
confidence: 93%
“…Anaemia occurred (haemoglobin < 7 g/dl) within the first few months of initiation of therapy. In majority of the patients, improvement in haemoglobin level was observed once zidovudine containing regimen was withdrawn which was similar to the study conducted by (Kaibalya, et al 2015). So, the red blood cell disorders could have been minimized by regular monitoring of blood parameters.…”
Section: Resultssupporting
confidence: 74%
“…8 This could be explained by the fact that Zidovudine is related to suppressions of bone marrow that leads to a reduction in the production of red blood cells and other types of blood cells in the bone marrow. 26 Another significant predictor of anemia among children with ART was under-nutrition which had 2.7 times at higher risk to develop anemia than normal nutritional status. The finding was in line with a study conducted in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“… 8 This could be explained by the fact that Zidovudine is related to suppressions of bone marrow that leads to a reduction in the production of red blood cells and other types of blood cells in the bone marrow. 26 …”
Section: Discussionmentioning
confidence: 99%